Prevalence and risk factors of chronic obstructive pulmonary disease in Bangladesh: A systematic review - Sutradhar, Ipsita; Gupta, Rajat Das; Hasan, Mehedi; Wazib, Amit; Sarker, Malabika (Cureus, 2022)
This article was published in the Cureus [© Copyright 2019 Sutradhar et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 3.0] and the definite version is available at: http://dx.doi.org/10.7759/cureus.3970 The Journal's website is at: https://www.cureus.com/articles/15943-prevalence-and-risk-factors-of-chronic-obstructive-pulmonary-disease-in-bangladesh-a-systematic-review#article-disclosures-acknowledgements